2004
DOI: 10.1051/vetres:2003040
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a single injection of dexamethasone-21-isonicotinate on the lymphocyte functions of dairy cows at two weeks post partum

Abstract: -Dexamethasone is a potent therapeutic for treatment of the fatty liver syndrome or primary ketosis in post partum dairy cows. Reservations exist, however, among practitioners with respect to the risk of immunosuppression induced by corticosteroids. The aim of this study was to investigate the effect of a single injection of dexamethasone-21-isonicotinate on distinct immune functions of postpartum dairy cows because only scarce information is available on the effects of corticosteroid preparations when adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
2
9
0
1
Order By: Relevance
“…This was in accordance with earlier studies where glucocorticoid injection resulted in a maked increase in fasted sheep (Fürll and Knobloch, 1994), goats (Sandner et al, 1990) and cattle (Thanasak et al, 2004). Glucocorticoids proven to result in hyperglycaemia through stimulation of gluconeogenesis and reduction of glucose consumption by blocking glucose uptake.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This was in accordance with earlier studies where glucocorticoid injection resulted in a maked increase in fasted sheep (Fürll and Knobloch, 1994), goats (Sandner et al, 1990) and cattle (Thanasak et al, 2004). Glucocorticoids proven to result in hyperglycaemia through stimulation of gluconeogenesis and reduction of glucose consumption by blocking glucose uptake.…”
Section: Resultssupporting
confidence: 92%
“…Fürll and Knobloch (1994) stated a considerable increase in glucose and insulin concentrations after dexamethasone injection in sheep fasted for five days. Thanasak et al (2004) also reported an increase in glucose and insulin levels after a single dose in cattle. Sander et al (1990) reported a 200 fold increase in insulin level in fasted goats after dexamethasone administration.…”
Section: Introductionmentioning
confidence: 87%
“…In fact, effect of dexamethasone on the WBC counts may depend on dose or animal kinds. Increased WBC counts were reported in female turkeys after dexamethasone treatment, but similar effect of dexamethasone was not observed in males (Huff et al 2015), and increased WBC counts were determined in cows (Thanasak et al 2004). These results may indicate dexamethasone directly affect WBC level in sheep and has no effect other hemogram values.…”
Section: Discussionmentioning
confidence: 60%
“…As a corticosteroid, dexamethasone affects the HPA axis (Rijnberk and Mol, 1997), and several studies conducted on cattle and veal calves have shown that such molecules might lead to leukocytosis, neutrophilia, eosinopenia, lymphopenia and monocytosis, as well as to an increase in the Neu/Lym ratio (Lan et al, 1995;Anderson et al, 1999;Thanasak et al, 2004). Oldham and Howard (1992) have shown that daily intramuscular injections of dexamethasone at 0.5 mg/kg per day in calves for 20 days resulted in neutrophilia and lymphopenia.…”
Section: Discussionmentioning
confidence: 99%